Regulatory evaluation and toxicological considerations of approved and emerging psoriasis therapies - Payal Kesharwani; Tripti Paliwal; Arya Kuhu Vishwapriya; Swapnil Sharma; Devesh U Kapoor (Next Research, 2026)

GWAS-based dissection of important grain mineral and anti-nutrient traits in a diverse set of pearl millet germplasm across multi-environments - S. Hemanth; Sumer Pal Singh; Tripti Singhal; Aavula Naveen; Sunaina Yadav; Chandan Kapoor; Satyam Sharma; H.A. Bhargavi; Thippeswamy Danakumara; David Jesse Jangala; Nirupma Singh; T. Nepolean; et al. (Journal of Cereal Science, 2026)

Neuroprotective role of cyanidin in Alzheimer’s and Parkinson’s disease: current insights and the road ahead - Bushra Bashir; Nandani Andotra; Prince Sharma; Tripti Sharma; Smriti Chauhan; Ankit Awasthi; Shareen Singh; Thakur Gurjeet Singh; Sachin Kumar Singh; Sukriti Vishwas (Inflammopharmacology, 2026)

Multi-environment stability analysis identifies wheat genotypes tolerant to terminal heat stress under varied nitrogen regimes - G. Andonissamy Daniel; Lukram Shantikumar; Sandeep Sharma; Tripti Tomar; Aman Khan; Revanth Ragul Arivanandham; Harikrishna; Anjali Anand; Alison R. Bentley; Matthew P. Reynolds; Renu Pandey (Plant Physiology Reports, 2026)

Emerging nanomaterial-based sensors for foodborne pathogen and toxin detection - Tripti Paliwal; Payal Kesharwani; Renu Yadav; Kanika Verma; Jaya Dwivedi; Swapnil Sharma (Food Research International, 2025)

Chitosan polyplexes for targeted gene delivery: From mechanisms to clinical applications - Radhika Joshi; Tripti Paliwal; Swapnil Sharma; Devesh U. Kapoor; Bhupendra G. Prajapati (Carbohydrate Polymers, 2025)

Metabolic Diversity of a Widely Distributed Tropical Freshwater Crab Is Not Underpinned by Genetic Differences - Lucy M. Turner; Christopher J. Thorpe; Michael Collins; Smrithy Raj; Tripti Shukla; John I. Spicer; Mairi E. Knight; Dheeraj Sharma; Krushnamegh Kunte (Journal of Biogeography, 2025)
Aim The aim of this study was to understand the interplay between local and regional factors as drivers of population physiological diversity in a tropical freshwater crab species. Location Western Ghats, south‐west India. Taxon Barytelphusa cunicularis, Brachyura, Crustacea. Methods We applied an integrative approach combining population genetics and whole animal physiology, using the tropical freshwater crab Barytelphusa cunicularis as our model species. We tested for effects of population location (e.g., latitude, altitude), season (as a proxy for rainfall and water temperature) and/or warming on indices of whole animal respiratory physiology (metabolic rate, MO 2 ) and hypoxic performance (P crit , i.e., the PO 2 at which routine MO 2 can no longer be sustained) in five widely distributed populations of this species. We also generated population genetic data (mtDNA COI and nDNA histone H3 sequences) to determine the extent of any population genetic structuring and/or cryptic species diversity present to verify that we were investigating a single species. Results Despite a high level of genetic structuring between the different populations of B. cunicularis examined, the genetic distances observed were consistent with intra‐ and not interspecific differences in freshwater crabs. Populations varied in the diversity of the physiological (MO 2 ) responses observed. There were significant effects of season and population on respiration in response to temperature and P crit in response to acute hypoxia. Main Conclusions We conclude that local environmental factors are important in shaping physiological diversity between populations in tropical freshwater species and systems. This highlights the need to include population‐level responses in any projections we make on how biodiversity will respond to ongoing and future environmental changes, including those caused by climate change.

Anti-adipogenic and anti-steatotic potential of edible pigment bixin and annatto seed extracts: LC-MS based bioactive profiling and in vitro biochemical validation - Sonakshi Puri; Sumit Kumar Mandal; Tripti Joshi; Nikita; Ayush Srivastava; Pankaj Kumar Sharma; P.R. Deepa (Food Bioscience, 2025)

Enhanced Red Luminescence in Dy3+/Eu3+ Co-doped Calcium Alumino Borosilicate Glasses for w-LED Applications - Videsh Kumar; Sheetal Kumari; Shristy Malik; Ravita; Tripti Sharma; Aman Prasad; A. S. Rao (Journal of Fluorescence, 2025)

Structure based exploration of mitochondrial alpha carbonic anhydrase inhibitors as potential leads for anti-obesity drug development - Ipsa Padhy; Tripti Sharma; Biswajit Banerjee; Sujata Mohapatra; Chita R. Sahoo; Rabindra Nath Padhy (DARU Journal of Pharmaceutical Sciences, 2024)

Desert legumes as sustainable sources of proteins and bioactive peptides: Technological insights into functional food development from underutilized plants - Shelly Chauhan; Tripti Joshi; Utkarsh Adhikari; Anagh Sinha; P.R. Deepa; Pankaj Kumar Sharma (Food and Humanity, 2024)

Nutraceutical and flavor profiles in underutilized desert legumes of India: gene editing strategies towards sustainable food development - Tripti Joshi; Hansa Sehgal; Sumit Kumar Mandal; Mukul Joshi; P. R. Deepa; Pankaj Kumar Sharma (Journal of Plant Biochemistry and Biotechnology, 2023)

Exploring the mechanisms and impacts of melatonin on fish colouration - Muhammad Mubashshir; Nabeel Ahmad; Tripti Negi; Renu Bala Sharma; Helen Nilsson Sköld; Mohd Ovais (Fish Physiology and Biochemistry, 2023)

Emerging Field of Nanotechnology in Environment - Vijya Laxmi; Nirjara Singhvi; Nabeel Ahmad; Shruti Sinha; Tripti Negi; Vipin Gupta; Muhammad Mubashshir; Adnan Ahmad; Sandeep Sharma (Indian Journal of Microbiology, 2023)

Arid/semi-arid flora as a treasure trove of bioactives and bioenergy: the case for underutilized desert legumes towards environmental sustainability - Tripti Joshi; Sumit Kumar Mandal; Vidushi Asati; Perinkulam Ravi Deepa; Pankaj Kumar Sharma (Environmental Science and Pollution Research, 2023)

Effect of Different Proportions of Phenolics on Antioxidant Potential: Pointers for Bioactive Synergy/Antagonism in Foods and Nutraceuticals - Tripti Joshi; P. R. Deepa; Pankaj Kumar Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Plasticity of photosynthetic performance of the Indian tree Butea monosperma TAUB. at three sites with different microclimates - Melanie Mikosch; Nilima Kumari; Tripti Sharma; Vinay Sharma; Arthur Gessler; Elke Fischer-Schliebs; Ulrich Lüttge (Photosynthesis Research, 2012)